Workshop model pembelajaran demokrasi guru sekolah dasar di Jawa Tengah - Hidayat, Muhamad Taufik; Arangga, Albi; Rohman, Muhammad Abdur; Rahmawati, Faradiyah Nurul; Saadah, Rina Ulwiyatus; Utomo, Arief Cahyo; Muhroji, Muhroji (Penamas: Journal of Community Service, 2021)
The aim of this community service is to provide a democracy learning model workshop for elementary school teachers in Central Java. This activity is to socialize and practice the skills of the democratic learning model at the elementary level. In this activity, 26 elementary school teachers participated by online (Zoom Application). This community service is carried out in the form of a workshop with the first stage in the form of lecturing, questions and answers, and discussions. While the next stage is in the form of practice. Based on the implementation of this community service, it can be concluded that: first, this workshop is able to improve the knowledge and skills of elementary school teachers in Central Java of democracy learning model. This workshop also produced a video product of the steps of the democracy learning model. This workshop was considered success because all participants participated fully.